ENHANCING CRITICAL THINKING THROUGH THE DEVELOPMENT OF A CRITICAL LISTENING TEACHING MODEL WITH STUDENTS' SELF-MEDIATED PODCAST: AN EXPERIMENTAL STUDY - Arif Suryo Priyatmojo; Issy Yuliasri; Abdurrachman Faridi; Charanjit Kaur Swaran Singh (English Review: Journal of English Education, 2025)
The study aimed to examine whether there is a significant difference in students' critical thinking skills before and after the implementation of a self-mediated podcast model in a critical listening class to improve critical thinking. Using a mixed-methods, quasi-experimental design, the study involved 67 fourth-semester English Education students at Universitas Negeri Semarang. The experimental group used the ARIPS (Analyze, Review, Revise, Record, Immediately Podcast, and Share) model while the control group received conventional instruction. Results analyzed through paired sample and independent t-tests demonstrated a statistically significant improvement in the experimental group's critical thinking skills (p < 0.001). The findings suggest that the integration of self-mediated podcasting effectively enhances students' critical thinking.